Delusion of Pregnancy as a Somatic-Type Delusional Disorder in a Young Male From the South of Iran - Reza Bidaki; Bonnie Bozorg; Mohammad Ayatollahi; Mehrdad Roozbeh (Baqiyatallah University of Medical Sciences, 2018)
Introduction: Delusion of pregnancy is a bizarre delusion in which one feels s/he is carrying a fetus. The etiology is unknown, but aloneness, masturbation, and stress may precipitate this disorder. Case Presentation: We introduce a young, single man who has delusions of pregnancy. This type of delusion is not a well-known disorder; based on investigated articles, this type of somatic delusion is rare. Conclusion: This was a chronic case, the exact cause and development of which was unknown. We suggest this phenomenon as a novel symptom. No similar case was found in the literature.